On the non‐ideal vibrating structures. Issue 1 (December 2014) - Chiroiu, Veturia; Donescu, Stefania; Dumitriu, Dan
Abstract In this work, analysis of the response to vibrations of a small building equipped with an electromechanical vibration absorber is investigated. The case of harmonic excitation with constant or time dependent frequencies is considered. The interaction between the structure and the energy source is analyzed via the Sommerfeld effect inside the resonance region. The resonance capture and the vibration reduction are displayed by the time history displacement of the last story. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)